Delving into the whirlwind: some exploratory notes on everyday life and gender - Chong, Eu Choong (Universiti Kebangsaan Malaysia, 2003)
This paper argues that the social science singeneral an main stream sociology in particular have long ignored everyday life as a the oretical problem. As a result, the social-scientific discourses on social life have become impoverished for it. The writer argues for the need to incorporate everyday life as one of the central component of analysis in sociology. However, the very qualities of everyday life, its pervasiveness, complexity and evanesce, have rendered this area opaque to conventional approaches of sociology. In addition, feminist research has alerted us to the fact that we experience everyday as gendered subjects that further complicates the matter. Here, the writer seeks to explore ways to render everyday life and the gender subjectivity of everyday life more amendable to investigation, particularly within the Malaysian context. The writer suggests that there exists a tradition that has specifically dealt with everyday life and gendered subjectivity of everyday life as a theoretical problem. It is the writer’s position that one can never truly produce the last word on this subject but rather a tentative first word where one can only extend an invitation for further investigation into this area.